PERAN KELEMBAGAAN GABUNGAN KELOMPOK TANI DALAM PENGELOLAAN HUTAN KEMASYARAKATAN - Alifia Putri Larasati; Christine Wulandari; Indra Gumay Febryano; Hari Kaskoyo (Jurnal Belantara, 2021)
Gapoktan institutions have important roles, including its functions to regulate community activities, individually or in groups, on managing community forests. This study aims to explain the management of HKm based on the role of gapoktan institutions. The research methodologies are interview and documentation study. The data obtained were analyzed descriptively. Results showed that institutionally Gapoktan has a complete administration and written rules regarding the management of HKm. Each farmer member is required to work on land with agroforestry patterns dominated by MPTS plants. Gapoktan has a farming business that functions to help market forest products. Farming management is divided into two, namely individual businesses and gapoktan businesses. Until now there has been no significant development of farming in the last two years. Therefore, the government needs to conduct counseling to increase knowledge about farming so that they can market forest products more optimally.